Measurement of compensatory arterial remodelling over time with serial coronary computed tomography angiography and 3D metrics . (1st September 2021) - van den Hoogen, Inge J; van Rosendael, Alexander R; Lin, Fay Y; Gianni, Umberto; Andreini, Daniele; Al-Mallah, Mouaz H; Budoff, Matthew J; Cademartiri, Filippo; Chinnaiyan, Kavitha; Hyun Choi, Jung; Conte, Edoardo; Marques, Hugo; et al.
Abstract: Aims: The magnitude of alterations in which coronary arteries remodel and narrow over time is not well understood. We aimed to examine changes in coronary arterial remodelling and luminal narrowing by three-dimensional (3D) metrics from serial coronary computed tomography angiography (CCTA). Methods and results: From a multicentre registry of patients with suspected coronary artery disease who underwent clinically indicated serial CCTA (median interscan interval = 3.3 years), we quantitatively measured coronary plaque, vessel, and lumen volumes on both scans. Primary outcome was the per-segment change in coronary vessel and lumen volume from a change in plaque volume, focusing on arterial remodelling. Multivariate generalized estimating equations including statins were calculated comparing associations between groups of baseline percent atheroma volume (PAV) and location within the coronary artery tree. From 1245 patients (mean age 61 ± 9 years, 39% women), a total of 5721 segments were analysed. For each 1.00 mm 3 increase in plaque volume, the vessel volume increased by 0.71 mm 3 [95% confidence interval (CI) 0.63 to 0.79 mm 3, P < 0.001] with a corresponding reduction in lumen volume by 0.29 mm 3 (95% CI −0.37 to −0.21 mm 3, P < 0.001). Serial 3D arterial remodelling and luminal narrowing was similar in segments with low and high baseline PAV ( P ≥ 0.496). No differences were observed between left main and non-left main segments, proximal and distal segments and side branch and non-side branch segments ( P ≥ 0.281). Conclusions: Over time, atherosclerotic coronary plaque reveals prominent outward arterial remodelling that co-occurs with modest luminal narrowing. These findings provide additional insight into the compensatory mechanisms involved in the progression of coronary atherosclerosis.